2019
DOI: 10.1111/tbj.13295
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral blocks in immediate breast reconstruction following mastectomy

Abstract: Background Postoperative pain remains a major challenge following immediate breast reconstruction with 40% of patients experiencing acute pain and up to 60% developing chronic pain. Paravertebral blocks (PVB's) have emerged as a promising adjunct to standard analgesic protocols. The aim of this study was to assess the utility of PVB's in immediate breast reconstruction following mastectomy. Methods A retrospective review of patients undergoing immediate breast reconstruction following mastectomy was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Hemodynamic instability or compromise, surgical stress response, poor postoperative pain control and delayed spontaneous respiratory recovery, many inflammatory mediators produced by white blood cells and endothelial cells can all cause pain, and such pain can be offset by endogenous opioids in peripheral termination of the nerve (29,30). Inflammation occurs in the trauma area, leading to the activation of pain receptors (31, 32).…”
Section: Gene Expression Resultsmentioning
confidence: 99%
“…Hemodynamic instability or compromise, surgical stress response, poor postoperative pain control and delayed spontaneous respiratory recovery, many inflammatory mediators produced by white blood cells and endothelial cells can all cause pain, and such pain can be offset by endogenous opioids in peripheral termination of the nerve (29,30). Inflammation occurs in the trauma area, leading to the activation of pain receptors (31, 32).…”
Section: Gene Expression Resultsmentioning
confidence: 99%
“…This finding is consistent with other studies on PVBs in implant-based reconstruction, which have also shown that opioid consumption is slightly reduced in patients receiving blocks. 15,17,25 For example, Stein et al 25 found that opioid use was 11 MMEs lower among patients who received PVBs than among those who did not. Our study, however, is the first to utilize propensity score matching to improve the comparability of patients who do or do not receive PVBs, thus providing more definitive evidence for the effect of PVBs on opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include TAP blocks, 21,22 Nmethyl-D-aspartate antagonists (gabapentin), 23 continuous local anesthesia pumps (On Q PUMP), 4,9 and paravertebral blocks. [24][25][26][27][28][29] Studies on the effect of TAP block on recovery after microvascular reconstruction have shown positive outcomes. [5][6][7][8] Therefore, our ERAS initially used TAP block with liposomal bupivacaine to target the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these baseline components, ERAS protocols can have certain unique components that account for improved outcomes. Examples include TAP blocks, 21,22 N -methyl- d -aspartate antagonists (gabapentin), 23 continuous local anesthesia pumps (On Q PUMP), 4,9 and paravertebral blocks 24–29 . Studies on the effect of TAP block on recovery after microvascular reconstruction have shown positive outcomes 5–8 .…”
Section: Discussionmentioning
confidence: 99%